What level of physical activity protects against premature cardiovascular death? The Caerphilly study. Issue 5 (1st May 2003) - Yu, S; Yarnell, J W G; Sweetnam, P M; Murray, L
Abstract : Objective: To examine the optimal intensity of leisure time physical activity (LTPA) to decrease the risk of all cause, cardiovascular disease (CVD), and coronary heart disease (CHD) mortality in a population sample of middle aged British men. Design: Prospective study of middle aged men with an 11 year follow up. Setting: A whole population sample of men from Caerphilly, South Wales, UK. Subjects: 1975 men aged 49–64 years without historical or clinical evidence of CHD at baseline examination. Main outcome measures: All cause, CVD, and CHD mortality. Results: Total (cumulative) LTPA had a graded, significant relation with all cause, CVD, and CHD mortality but no trend with cancer deaths. When different intensities of activity were considered, light and moderate intensity LTPA had inconsistent and non-significant relations with all cause, CVD, or CHD mortality whether adjusted only for age or for other cardiovascular risk factors. In contrast a significant dose–response relation was found for heavy intensity LTPA for all cause, CVD, and CHD mortality fully adjusted for other risk factors. Conclusions: These data suggest that, in a population of men without evidence of CHD at baseline, only leisure exercise classified as heavy or vigorous was independently associated with reduced risk of premature death from CVD.